RECRUITMENT AND SELECTION: UNDERSTANDING THE SCHOOL'S STRATEGY IN REALIZING SUPERIOR EDUCATIONAL STAFF PERFORMANCE - Pujiono, Pujiono; Yetri, Yetri; Amiruddin , Amiruddin (Universitas Nurul Jadid, 2022)
This study aims to analyze the strategy of recruitment and selection of teaching staff in order to achieve the goals of the institution. The method used in this study is a qualitative descriptive method, which describes existing phenomena. As for data collection techniques using observation, interviews and document study. Researchers conducted interviews with school principals, deputy principals, chairs and secretaries of the Muhammadiyah Elementary and Middle Education Council (MPDM) in Metro City. The results of the study show that the strategy for recruiting and selecting educators has been good. This recruitment activity begins with planning the needs of educators, namely by analyzing the needs of existing teachers, announcement of vacancies for educators, requirements that must be met by prospective educators, selection with various tests, interviews and determining teacher acceptance. The strategy used can be said to be effective for schools, this is proven by the very good quality of teaching staff obtained as expressed by the principal as the executor and decision maker in teacher recruitment activities.